Se-duction is not sex-duction: Desexualizing and de-feminizing hysteria - Mancini, Milena; Scudiero, Martina; Mignogna, Silvio; Urso, Valentina; Stanghellini, Giovanni (Frontiers in Psychology, 2022)
The psychopathological analysis of hysteria is a victim of narrow conceptualizations. Among these is the inscription of hysteria in the feminine sphere, about body and sexuality, which incentivized conceptual reductionism. Hysteria has been mainly considered a gender pathology, mostly exclusively female, and it has been associated with cultural and/or religious features over time rather than treated as a psychopathological world. Hysteria was dominated by conceptual inaccuracies and indecisions not only in terms of clinical features but also in terms of its definition. For this reason, it seems necessary to “undress” hysteria from this feminization, sexualization, and corporealization of which it has been abundantly clothed over the years. “Undressing” hysteria will make possible reconfiguring, deconstructing, and detaining the explanatory-causal model of Charcot and Freud. However, if we take out this cultural heritage, the stigma accompanying this diagnosis and the weight of the enormous historical tradition that hysteria brings, the hysterical world continues to constitute a domain full of complexity and nosographic challenges. Over time, hysteria has been considered as a sum of psychological behaviors and states illustrated by drama, mystery, or falsity. The trouble in understanding the multiple somatic manifestations characterizing this clinical condition did not help to clarify the matter but created several controversies and confusion. In the current nosography the personological component of hysteria has been separated from its symptomatic manifestation, respectively, in both Histrionic Personality Disorder and Conversion Disorder categories. The overmentioned segmentation carried out by descriptive nosography certainly does not play in favor of a unitary understanding of the phenomenon and, consequently, of daily clinical practice. Clinical complexity can be grasped and deciphered only if the symptom is inscribed in the patient's life-world and his/her subjective life history, thinking of the clinical practice in terms of a structural aggregation of a homogeneous set of phenomena constituting together a specific way to being-in-the-world. The starting point of this paper is to grasp the evident and visible modalities characterizing this life-world and dwell on them, taking care not to confuse the point of origin with the point of expression.